The Impact of the Functional Transformation of Buddhist Temples in East Java on Tourists' Spiritual Experiences - ayuning wulan; Lery Prasetyo; Eko Siswoyo (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2026)
Purpose: This study aims to analyze how the transformation of the functions of Jago Temple, Sumberawan Temple, Brahu Temple, and Gentong Temple as tourist destinations affects the spiritual experience of tourists when doing activities in these temples. Method: This study uses a descriptive qualitative approach. Data was collected through observation, documentation, and in-depth interviews with 6 informants who had visited one of the research sites and carried out spiritual activities during the visit. Data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawn, while data validity is maintained through triangulation of sources and methods. Result: The transformation of the temple's function results in a hybrid space that combines sacred and touristic values. Tourism activities such as photography and recreation show the commodification of culture, but they do not completely eliminate spiritual value. Tourists' spiritual experiences are diverse and subjective, such as a sense of calm, self-reflection, and contemplation without formal rituals. Environmental factors such as density and noise affect the quality of the experience. Contribution: This research shows that the transformation of the function of the temple does not eliminate the sacred, but rather transforms it into a more personal and contextual form of spirituality. The result also explains that the spirituality of tourists can still be formed through reflective experiences even though the temple space has undergone commercialization and increased tourist activities.